2021
DOI: 10.36618/merpati.v3i1.1520
|View full text |Cite
|
Sign up to set email alerts
|

Pendampingan Kampus Mengajar Angkatan 1 Dalam Lingkup Sekolah Di Daerah 3t

Abstract: Pandemi telah memukul banyak sektor termasuk pendidikan, namun kita harus bergerak maju. Saatnya bagi bangsa ini untuk bergerak bersama demi tercapainya tujuan yang sama untuk kebangkitan Sumber Daya Manusia. Saat ini kreativitas dan inovasi menjadi kata kunci penting untuk memastikan pembangunan Indonesia yang berkelanjutan. Para mahasiswa yang saat ini belajar di Perguruan Tinggi, harus disiapkan menjadi pembelajar sejati yang terampil, lentur dan ulet (agile learner). Kebijakan Merdeka Belajar – Kampus Merd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
(1 reference statement)
0
3
0
1
Order By: Relevance
“…After reviewing nearly all existing literature on Kampus Mengajar, the researchers found that most of the published literature focused primarily on how the program is run on Java Island. The most predominant province in reporting the impact of their program is East Java (Anwar, 2021;Ashari et al, 2022;Bali et al, 2022;Rachman et al, 2021;Rosita & Damayanti, 2021;Salsabila et al, 2022;Setyadi et al, 2021;Tsamroh et al, 2021), closely followed by West Java (Khairunnisa & Kurniawan, 2021;Mulyati et al, 2021;Safaringga et al, 2022;Usral et al, 2022;Utami, 2021). Research also covers the program in Central Java (Prasandha & Utomo, 2022;Pristya et al, 2022;Santoso et al, 2022;Widiyono et al, 2021;Widjanarko et al, 2021), Jakarta (Anugrah, 2021;Fatonah et al, 2021;Lestari et al, 2023;Rahmadani et al, 2022), Bengkulu (Nurhasanah & Nopianti, 2021), West Nusa Tenggara (Hikmawati et al, 2022), West Sumatra (Rahim & Suryani, 2022), North Sumatra (Martina et al, 2022) and South Sumatra (Hendrowati & Sunanto, 2021;Khotimah et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing nearly all existing literature on Kampus Mengajar, the researchers found that most of the published literature focused primarily on how the program is run on Java Island. The most predominant province in reporting the impact of their program is East Java (Anwar, 2021;Ashari et al, 2022;Bali et al, 2022;Rachman et al, 2021;Rosita & Damayanti, 2021;Salsabila et al, 2022;Setyadi et al, 2021;Tsamroh et al, 2021), closely followed by West Java (Khairunnisa & Kurniawan, 2021;Mulyati et al, 2021;Safaringga et al, 2022;Usral et al, 2022;Utami, 2021). Research also covers the program in Central Java (Prasandha & Utomo, 2022;Pristya et al, 2022;Santoso et al, 2022;Widiyono et al, 2021;Widjanarko et al, 2021), Jakarta (Anugrah, 2021;Fatonah et al, 2021;Lestari et al, 2023;Rahmadani et al, 2022), Bengkulu (Nurhasanah & Nopianti, 2021), West Nusa Tenggara (Hikmawati et al, 2022), West Sumatra (Rahim & Suryani, 2022), North Sumatra (Martina et al, 2022) and South Sumatra (Hendrowati & Sunanto, 2021;Khotimah et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Looking at studies on Kampus Mengajar Program and its implementation for target schools, the results generally illustrate that this program is highly effective in overcoming the declining quality of education in the fields of reading, writing, arithmetic, technology, and administration, which are the four main issues to be addressed. Yet, the following studies by Anugrah (2021); Anwar (2021); Bali et al, (2022); Etika et al, (2021); Hikmawati et al, (2022); Mulyati et al, (2021) and Nurhasanah & Nopianti (2021) have focused less on examining the issues and more on describing how they implemented the program with an effective outcome picture as if this Kampus Mengajar Program was far from failing in its application.…”
Section: Introductionmentioning
confidence: 99%
“…Program Kampus Mengajar juga memberikan kesempatan bagi mahasiswa untuk menerapkan ilmu yang telah didapat di perkuliahan untuk memecahkan berbagai masalah yang ditemukan di sekolah. Melalui partisipasi aktif dalam Program Kampus Mengajar, mahasiswa menjadi lebih proaktif, percaya diri, dan mampu berkolaborasi dengan para guru serta rekan sejawat dengan baik (Mulyati et al, 2021).…”
Section: Pendahuluanunclassified
“…There is no shortage of studies that have alluded to one of these challenges of online education during the pandemic, such as low internet bandwidth resulting in frequent interruptions of audiovisual communication (Agung et al, 2020;Octaberlina & Muslimin, 2020), simple lack of internet access due to the school or students' disadvantaged area (Chirinda et al, 2021;Mukherjee et al, 2021), lack of student discipline (Kholili, 2021;Syahdan & Ali, 2022), lack of social interaction (Adnan & Anwar, 2020;Irawan et al, 2020), teachers' and lecturers' inconsistent adaptability with the offline-to-online learning style (Putri et al, 2020;, and many more. Previous studies have frequently emphasized how facilities and infrastructure uneven distribution is not the only obstacle in the process of implementing this online learning policy, but there are also obstacles and limitations stemming from the teaching staff who may not have the ability and accessibility to operate and use cellphones or laptops (Mulyati et al, 2021) or have difficulty in leveraging the available online resources to creatively address the numerous problems of online learning (Khairuddin, 2020).…”
Section: Kompascommentioning
confidence: 99%